2015
DOI: 10.1111/odi.12325
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anti‐hypertensives and type 2 diabetes on salivary flow and total antioxidant capacity

Abstract: Enalapril is not xerogenic but is antioxidant, which moderately reduces the risk of xerogenic effect development even in the presence of DM type 2. However, metoprolol and drug combinations exhibit xerogenic effect. In DM type 2, xerogenic effect of all drugs was pronounced except of metoprolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…On the other hand, no differences were found between the subgroup of apparently healthy subjects (without drug treatment) and the subgroup receiving pharmacotherapy with regard to TAC/UA parameters. The use of anti-hypertensives or the presence of diabetes mellitus type 2 have been found to have little effect on salivary TAC in the few previous studies in this area [37,38].…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, no differences were found between the subgroup of apparently healthy subjects (without drug treatment) and the subgroup receiving pharmacotherapy with regard to TAC/UA parameters. The use of anti-hypertensives or the presence of diabetes mellitus type 2 have been found to have little effect on salivary TAC in the few previous studies in this area [37,38].…”
Section: Discussionmentioning
confidence: 88%
“…Djukic et al (16) showed in a population of 387 hypertensive subjects that hypertension combined to diabetes promoted a significant salivary flow rate decrease that was dependent of the type of anti-hypertensive drug administrated during the treatment. In our data, salivary flow rate was also significantly different for diabetic patients (DM or DM+HAS group), which had salivary flow levels lower than 0.7 mL/min, while control and HAS individuals had normal flow condition (1-3 mL/min).…”
Section: Tgfβ1 In Diabetic and Hypertensive Patientsmentioning
confidence: 99%
“…This review showed that the most frequent oral ADR is xerostomia, and the most reported culprit drugs with significant results are antihypertensive medications (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the researchers unraveled that enalapril is an independent factor which is well capable of moderately reducing the risk of development of xerostomia; while with sharp contrast metoprolol is an independent risk factor for development of xerostomia. More impressive, combinations of enalapril with metoprolol and/or hydrochlorothiazide are not independent risk factors (19).…”
Section: Xerostomia and Hyposalivationmentioning
confidence: 99%